Approaches to the development of environmentally friendly and resource-saving technology for solar-grade silicon production. (2019) - Karabanov, Sergey M.; Suvorov, Dmitriy V.; Tarabrin, Dmitry Y.; Slivkin, Evgeniy V.; Karabanov, Andrey S.; Belyakov, Oleg A.; Trubitsyn, Andrey A.; Serebryakov, Andrey
ABSTRACT: Currently, the main material for the production of solar cells is still silicon. More than 70% of the global production of solar cells are silicon based. For solar-grade silicon production the technologies based on the reduction of silicon from organosilicon compounds are mainly used. These technologies are energy-consuming, highly explosive and unsustainable. The present paper studies the technology of purification of metallurgical-grade silicon by vacuum-thermal and plasma-chemical treatment of silicon melt under electromagnetic stirring using numerical simulation and compares this technology with the existing ones (silane technologies and Elkem Solar silicon (ESS) production process) in terms of energy consumption, environmental safety and the process scalability. It is shown that the proposed technology is environmentally safe, scalable and has low power consumption. The final product of this technology is multicrystalline silicon, ready for silicon wafer production.